Characterization of the chloroplast genome of Osbeckia stellata (Melastomataceae). Issue 1 (2nd January 2019) - Liang, Rifan; Ruan, Fei; Zhi, Xueke; Zhou, Qiujie
Abstract: Osbeckia stellata (Melastomataceae) is a shrub distributed in the South. Although many species of Osbeckia have important medicinal value, the phylogenetic position of Osbeckia within the family Melastomataceae remains unclear. Osbeckia stellata is one of the most widespread species in this genus. Here, we reported and characterized the complete chloroplast genome sequence of O. stellata assembled from Illumina sequencing reads. The chloroplast genome size is 156, 372 bp, containing a large single copy (LSC) region of 85, 741 bp, a short single copy (SSC) region of 17, 115 bp, and a pair of inverted repeats (IRs) of 26, 758 bp. We predicted a total of 136 genes consisting of 86 protein-coding genes, 48 tRNA genes, and 8 rRNA genes. Phylogenetic analysis showed that O. stellata was sister to Melastoma candidum .